Application of shot peening to improve fatigue properties via enhancement of precipitation response in high-strength Al–Cu–Li alloys - Michal Jambor; Libor Trško; Ivo Šulák; Filip Šiška; Sara Bagherifard; Mario Guagliano; Zuzana Florková (Journal of Materials Research and Technology)
This paper investigates the role of a hybrid treatment considering severe shot peening as a pre-treatment to age-hardening in enhancing the fatigue properties of an advanced high-strength Al–Cu–Li alloy. The alloy was subjected to severe shot peening with a combination of two different heat treatment regimes, aiming for microstructural modification to promote precipitation of heterogeneously nucleating phases. The effects of different treatments based on combined ageing and severe shot peening on residual stresses, hardness, microstructural characteristics, and fatigue properties were evaluated and critically discussed. The results have shown that in the case of heat treatment regimes at which the formation of heterogeneously nucleating T1 precipitates occurs, the application of severe shot peening prior to ageing results in significant refinement of strengthening particles, enhancing the fatigue properties in the short and medium fatigue lifetimes.